Legal aspects of regional autonomy in Spain = Prawne aspekty autonomii regionalnej w Hiszpanii - Wlaźlak, Katarzyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The experiences of regional autonomy in Spain encourage to make the diagnosis of the current political changes, as well as indicate possible scenarios related to the constitutional and legal future of the state. In this paper the concept of regional autonomy was defined, including showing the differences between the autonomous region and the region self-government, and the European countries with a common regional autonomy, and autonomy as an exception.
Keywords: regional autonomy; regions in Spain; the autonomous statutes; Catalonia; Basque Country; striving for independence; autonomia regionalna; regiony w Hiszpanii; statuty autonomiczne; Katalonia; Kraj Basków; dążenia niepodległościowe